Strategic and policy issues arising from the Easter 1998 floods delegate information : Wednesday 17 March 1999. (Thomas Telford, 1999)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 17 March 1999.